Sulfur isotope analysis by MC-ICP-MS and application to small medical samples. Issue 4 (7th March 2016) - Albalat, Emmanuelle; Telouk, Philippe; Balter, Vincent; Fujii, Toshiyuki; Bondanese, Victor Packy; Plissonnier, Marie-Laure; Vlaeminck-Guillem, Virginie; Baccheta, Justine; Thiam, Ndiémé; Miossec, Pierre; Zoulim, Fabien; Puisieux, Alain; et al.
Abstract : A new technique allows the precise measurement of sulfur isotopes by MC-ICP-MS in a large number of small biological samples. Abstract : We describe a technique of S isotope analysis in sulfate form with the first separation stage involving anion-exchange and the second stage of mass-spectrometric analysis by MC-ICP-MS using standard-sample-standard bracketing. Ammonium in 1 : 1 stoichiometric proportion with sulfate was used to improve transmission and stability and to avoid cone and membrane clogging by condensable species. The working resolution of ∼9000 allowed the main interferences, notably 32 SH on 33 S, to be resolved. The matrix effect caused by phosphorus present in biological samples is negligible for S/P ratios ≥10: our chemical protocol allows S/P ≥ 150 to be routinely achieved. Replicate measurements of S standard solutions give values of isotopic abundances within errors of accepted values and demonstrate a reproducibility of ±0.10‰ for δ 34 S and ±0.15‰ for δ 33 S (2s). The technique is adequate for quantities as small as 10 nanomoles. We investigated the δ 34 S of 110 samples of cancer patients and 10 samples of rheumatoid arthritis patients. We avoided the use of blood collection tubes with sulfate-containing heparin. Sulfur in serum is transported by albumin and fibrinogen. Most serum and plasma δ 34 S values fall within a narrow interval of ∼1‰ around a mean δ 34 SVCDT of ∼6.0‰. The δ 34 S values of total blood, serum, and plasma are very similar. Despite the short turnover time of albumin and fibrinogen, S is surprisingly well regulated. Subtle variations of 0.2–0.3‰ around the mean value can be assigned to sex and age, with sulfur in male and adult samples tending to be heavier than in their female and juvenile counterparts. This narrow range of variations across the spectrum of a large number of individuals not selected for controlled dietary habits seems paradoxical. In general, breast and prostate cancer and rheumatoid arthritis have very little effect on the average serum δ 34 S, but increase the scatter of values. We confirm that the serum of patients affected by liver cancer and other pathologies is depleted of albumin-born sulfur. While sulfur in the serum of patients with non-malignant liver pathologies tends to be isotopically light, the serum δ 34 S of medicated hepatocellular carcinoma patients tends to be at the high end of control values.